Current approach to Waldenström Macroglobulinemia - Gayathri Ravi (Cancer Treatment and Research Communications, 2022)
Waldenström Macroglobulinemia (WM) is a unique, low grade, IgM lymphoplasmacytic lymphoma with a heterogeneous clinical course. A paucity of high-grade evidence from large phase 3 trials remains a major issue in the field despite a rapidly expanding therapeutic armamentarium against WM. Prior knowledge of the patients’ MYD88L265P and CXCR4 mutation status aids in treatment decision making if Bruton's tyrosine kinase (BTK) inhibitor therapy is being considered. Head-to head comparative data to inform optimal approach are lacking, and a particularly vexing issue for the clinicians is choosing between fixed-duration bendamustine-rituximab (BR) therapy and an indefinite BTK inhibitor-based regimen, given that both approaches are well tolerated and effective, particularly for the patient population harboring MYD88L265P mutation. For the patients with MYD88WT genotype, chemo-immunotherapy such as BR is preferred, although zanubrutinib, a potent second generation BTK inhibitor, with its reduced off target effects and greater BTK occupancy compared to its predecessor, ibrutinib, has also recently shown activity in MYD88WT WM. This review summarizes the current literature pertaining to the diagnosis, prognosis, and the treatment of WM.